Randomized phase II study of fulvestrant and erlotinib compared with erlotinib alone in patients with advanced or metastatic non-small cell lung cancer. (September 2018) - Garon, Edward B.; Siegfried, Jill M.; Stabile, Laura P.; Young, Patricia A.; Marquez-Garban, Diana C.; Park, David J.; Patel, Ravi; Hu, Eddie H.; Sadeghi, Saeed; Parikh, Rupesh J.; Reckamp, Karen L.; Adams, Brad; et al.
Highlights: Phase II trial assessed antitumor efficacy of fulvestrant plus erlotinib in NSCLC. ORR was 16.4% for combination arm versus 12.1% for erlotinib alone arm. PFS and OS numerically favored the combination treatment arm versus erlotinib arm. In EGFR WT patients, but not EGFR mutant patients, fulvestrant plus erlotinib increased PFS. Dual therapy benefit in EGFR WT patients may be due in part to greater HR positivity. Abstract: Objectives: This open-label, randomized phase II trial evaluated antitumor efficacy of an antiestrogen, fulvestrant, in combination with human epidermal growth factor receptor (EGFR) inhibitor, erlotinib, in advanced non-small cell lung cancer (NSCLC) patients. Materials and Methods: Patients with advanced or metastatic NSCLC, ECOG 0–2, previous chemotherapy unless patient refusal, and no prior EGFR-directed therapy were randomized 2:1 to erlotinib 150 mg oral daily plus 500 mg intramuscular fulvestrant on day 1, 15, 29 and every 28 days thereafter or erlotinib alone 150 mg oral daily. The primary end point was objective response rate (ORR); secondary endpoints included progression free survival (PFS) and overall survival (OS). Results: Among 106 randomized patients, 100 received at least one dose of study drug. ORR was 16.4% (11 of 67 patients) for the combination versus 12.1% (4 of 33 patients) for erlotinib (p = 0.77). PFS median 3.5 versus 1.9 months [HR = 0.86, 95% CI (0.52–1.43), p = 0.29] and OS median 9.5 versus 5.8 months [HR = 0.92, 95% CI (0.57–1.48), p = 0.74] numerically favored the combination. In an unplanned subset analysis, among EGFR wild type patients (n = 51), but not EGFR mutant patients (n = 17), median PFS was 3.5 versus 1.7 months [HR = 0.35, 95% CI (0.14-0.86), p = 0.02] and OS was 6.2 versus 5.2 months [HR = 0.72, 95% CI (0.35–1.48), p = 0.37] for combined therapy versus erlotinib, respectively. Notably, EGFR WT patients were more likely to be hormone receptor-positive (either estrogen receptor α- and/or progesterone receptor-positive) compared to EGFR mutant patients (50% versus 9.1%, respectively) (p = 0.03). Treatment was well tolerated with predominant grade 1–2 dermatologic and gastrointestinal adverse effects. Conclusion: Addition of fulvestrant to erlotinib was well tolerated, with increased activity noted among EGFR wild type patients compared to erlotinib alone, albeit in an unplanned subset analysis.